2016
DOI: 10.1371/journal.pone.0147855
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Relevant to Pesticides and Biology from Global Transcriptome Data of Monochamus alternatus Hope (Coleoptera: Cerambycidae) Larvae

Abstract: Monochamus alternatus Hope is the main vector in China of the Pine Wilt Disease caused by the pine wood nematode Bursaphelenchus xylophilus. Although chemical control is traditionally used to prevent pine wilt disease, new strategies based in biological control are promising ways for the management of the disease. However, there is no deep sequence analysis of Monochamus alternatus Hope that describes the transcriptome and no information is available about gene function of this insect vector. We used next gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 143 publications
0
25
1
Order By: Relevance
“…The specific function of these unigenes could be clarified by six database annotations, especially GO classification, KEGG pathways, and COG terms. Unlike the minor ratio of "cellular component" (28.38%) in previous transcriptome analysis in M. alternatus GO annotation (Wu et al, 2016), this category (45.92%) was predominant in our study, which implied that most of the cells required being repaired after heat stress (Howard et al, 2011;Li et al, 2015;. In addition, more KEGG pathways and COG terms related to protein activity and signal transduction were also different from transcriptome data of this beetle treated with insecticide, which all suggested that stress-response mechanisms were diverse in M. alternatus.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The specific function of these unigenes could be clarified by six database annotations, especially GO classification, KEGG pathways, and COG terms. Unlike the minor ratio of "cellular component" (28.38%) in previous transcriptome analysis in M. alternatus GO annotation (Wu et al, 2016), this category (45.92%) was predominant in our study, which implied that most of the cells required being repaired after heat stress (Howard et al, 2011;Li et al, 2015;. In addition, more KEGG pathways and COG terms related to protein activity and signal transduction were also different from transcriptome data of this beetle treated with insecticide, which all suggested that stress-response mechanisms were diverse in M. alternatus.…”
Section: Discussionmentioning
confidence: 65%
“…False discovery rate (FDR) < 0.01 was marked as * * . study had analyzed the RNA-seq data of larval sawyer beetle treated with insecticide (Wu et al, 2016). Here, we detected 33,060 coding sequences in M. alternatus and observed 806 DEGs after heat treatment, which could contribute to underlying tolerant events in M. alternatus.…”
Section: Discussionmentioning
confidence: 90%
“…Stress from virus attack, starvation, host plant defences, temperature and oxidative factors lead to their overexpression; thus this class of proteases are promising candidates as targets . In researching the genetic background in control with pesticides of the beetle Monochamus alternates (main vector in China of the pine wilt disease), cathepsin B, cysteine peptidases, neuropeptides and serine peptidases were found to be important in growth, reproduction behaviour and other physiological processes . Thus, it was considered that these proteins could be suitable as targets for research into control strategies.…”
Section: Opportunities For Management Strategies Using Intracellular mentioning
confidence: 99%
“…56 In researching the genetic background in control with pesticides of the beetle Monochamus alternates (main vector in China of the pine wilt disease), cathepsin B, cysteine peptidases, neuropeptides and serine peptidases were found to be important in growth, reproduction behaviour and other physiological processes. 57 Thus, it was considered that these proteins could be suitable as targets for research into control strategies. Although a range of cellular proteins are upregulated when stressed insects become resistant, 17 the selection of the proteases as targets may be a preferred starting point, although not necessarily the only option.…”
Section: Intracellular Proteases As Targets 521 Enzyme Inhibitorsmentioning
confidence: 99%
“…Within the beetle, the nematode is exposed to the beetle's innate defence system, where it presents interspecies response to maintain the coexistence; therefore, the interaction between the parasitic nematode and its vector is noticeable (Zhao et al ., ; Zhao et al ., ; Zhao et al ., ). Previous studies have analyzed the RNA‐seq data of larval sawyer beetle (the 3rd instar larvae, the 4th instar larvae and pupal stage) treated with insecticide, which generously described putative insecticide resistance‐related genes, providing possible future insect control targets and immune‐related molecules (Wei et al ., ; Lin et al ., ; Lin et al ., ,b; Wu et al ., ). However, the knowledge of the M. alternatus immune response to B. xylophilus is almost blank at the cellular and molecular levels.…”
Section: Introductionmentioning
confidence: 97%